Analisis Keamanan Website Shih Ka Plastic Boxes Factory Terhadap Ancaman SQL Injection - Muhsinin, Muhammad Muhsinin; Mukhammad Said Riza Zudi; Yekti Adi Prasetyo; Ahmad Maulana Arif; Susanto (SOTVI - Society of Visual Informatics, 2025)
This study discusses security vulnerabilities in web applications, focusing on SQL injection attacks. With the increasing number of internet users and sensitive data being managed, system security on websites has become crucial. This research uses SQLmap to identify and explore potential attacks on the Shih ka Plastic Boxes Factory website. The findings reveal significant security gaps due to insufficient input validation. It was found that attackers could easily access sensitive data through the exploitation of these vulnerabilities. Additionally, recommendations for security improvements are suggested, including the implementation of strict input validation and the use of prepared statements to protect the database.